Question about the Ethics of Yalta Agreements in 1945. Archaeology of Power in Historiographical Discourses - Shevchenko, Oleg Konstantinovich (Conatus - Journal of Philosophy, 2019)
The Crimea (Yalta) Conference is by all means an extremely complex historical event. Any attempt to estimate its role and significance without analyzing its ethical components would unavoidably result in unduly simplifying the historical reality of the time, as well as in forming erroneous assumptions that would necessarily be used in the analysis of the causes of Cold War. A thorough examination will show that as far as the ‘ethical’ issues are concerned, there are significant developments with regard to general methodology, as well as its application to the sources. Generations of historians who have addressed the issue of Yalta Conference, although they have not been able to form a scientific, distinct ‘ethical’ tradition so far, have developed all the necessary prerequisites for its establishment. This is evident in the possibility of segmenting the issue in two parts on the one hand, and on the other in the availability of sufficient sources, structured databases, and selected outstanding works. Still, there are no studies about the Yalta Conference so far that address exclusively ethical issues concerning ‘good’ and ‘evil,’ ‘morality,’ ‘duty,’ and ‘honor.’ Although historiographical approaches are to a large extent dependent upon ethical viewpoints, in the case of Yalta agreements so far there have been no techniques available, so as to connect historical accounts with ideology, and historical facts with their philosophical background. In a sense, the situation is quite the same as it is with the study of prehistory: although there is an abundance of data and facts that can be primarily processed, there are no methodological guidelines, nor any devices to classify and explain them. This is also typical for any question raised about the ethics of the Yalta agreements in February 1945.